Contamination profiles and potential health risks of organophosphate flame retardants in PM2.5 from Guangzhou and Taiyuan, China. (January 2020) - Chen, Yanyan; Song, Yuanyuan; Chen, Yi-Jie; Zhang, Yanhao; Li, Ruijin; Wang, Yujie; Qi, Zenghua; Chen, Zhi-Feng; Cai, Zongwei
Graphical abstract: Highlights: OPFRs were detected ubiquitously in PM2.5 from Guangzhou and Taiyuan, China. Cl-OPFRs such as TCEP and TCPP were the predominant contaminants in PM2.5 . PM2.5 -bound OPFRs could induce the death of BEAS-2B cells. PM2.5 in Taiyuan had strong redox activities for ROS production. Minimum health risks to both toddlers and adults by PM2.5 -bound OPFRs were found. Abstract: Organophosphate flame retardants (OPFRs) are emerging contaminants in recent years. They can be present in the atmospheric fine particle (PM2.5 ), leading to potential adverse effects on humans. In this study, the concentrations and in vitro toxicities of OPFRs in PM2.5 samples were investigated for one year at Guangzhou and Taiyuan in China. Eleven OPFRs, including chloro-, aryl-, and alkyl-substituted OPFRs, were detected at total concentrations ranging from 3.10 to 544 ng m −3 . Chloro-substituted OPFRs were the dominant contaminants. Based on the statistical analysis, the same contamination sources of all OPFRs were found except for tris(butoxyethyl) phosphate (TBOEP) and triethyl phosphate (TEP), which may come from traffic emission. The results of cell viability and dithiothreitol assays indicated that OPFRs and PM2.5 could induce the death of normal lung epithelial cells and the production of reactive oxygen species (ROS), respectively. According to the redundancy analysis, the distribution of OPFRs was significantly related to the PM2.5 concentrations and indirectly associated with ROS production induced by PM2.5 from Taiyuan. Exposure to PM2.5 -bound OPFRs in Guangzhou and Taiyuan only posed minimum health risks to both toddlers and adults. These findings could provide important evidence to better clarify the contamination profiles and human health risks of OPFRs in atmospheric fine particles.